Kearifan Lokal dalam Novel Ikhtiar Cinta dari Adonara Karya J.S Maulana - Mulyani, Mimi; Ngibadiyah, Nurul; Liana, Novi Izmi (Universitas Negeri Semarang, 2022)
Literary work is an imaginative form of the author about the reality of the lives of local people. In the creation of literary works the authors photographed real life, including raising the local wisdom values of the culture of local people in the background of the story. Local wisdom should be kept and kept preserved, one of which explores the values of wisdom on cultural elements in the novel. The approach in this study is a qualitative speech with a descriptive method of analysis. The source of the data used is derived from J. S. Maulana's Endeavar Cinta from Adonara, with a study object of local wisdom reflected in cultural elements. The data is collected by the library study methods and the collection techniques are read, mark and classify. The data analysis method used is a descriptive analytical method.